UPAYA MENINGKATKAN KESEIMBANGAN PESERTA DIDIK KELAS VI MELALUI PERMAINAN KELERENG DI MIN 41 BIREUEN - Luthfia, Hilma; Rudy Juli Saputra; Rahmi Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the balance abilities of sixth-grade students at MIN 41 Bireuen through the implementation of a marble-carrying game in Physical Education, Sports, and Health (PJOK) learning. The background of this research is the low balance skills of students, as indicated by the low percentage of learning mastery achieved during the preliminary observation. This study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of planning, acting, observing, and reflecting stages. The research subjects consisted of 10 sixth-grade students at MIN 41 Bireuen. Data were collected through observation, performance tests, questionnaires, and documentation. The findings revealed a significant improvement in students’ balance abilities in each cycle. The percentage of learning mastery increased from 20% in the pre-action stage to 60% in Cycle I and further increased to 90% in Cycle II. Furthermore, the activities of both teachers and students showed improvement and reached the predetermined success indicators. Students also gave positive responses to the implementation of the marble-carrying game during learning activities. Therefore, it can be concluded that the marble-carrying game is effective in improving the balance abilities of sixth-grade students at MIN 41 Bireuen and creating an enjoyable and active learning atmosphere.